Tertiary sulphonamide derivatives as dual acting small molecules that inhibit LSD1 and suppress tubulin polymerisation against liver cancer - Lijuan Ding; Feng Wei; Nanya Wang; Yue Sun; Qiang Wang; Xia Fan; Ling Qi; Shudong Wang (Taylor & Francis Group, 2021)
A series of tertiary sulphonamide derivatives were synthesised and evaluated for their antiproliferative activity against liver cancer cell lines (SNU-475, HepG-2, and Bel-7402). Among these tertiary sulphonamides, compound 17a displayed the best anti-liver cancer activity against Bel-7402 cells with an IC50 value of 0.32 μM. Compound 17a could effectively inhibit tubulin polymerisation with an IC50 value of 1.27 μM. Meanwhile, it selectively suppressed LSD1 with an IC50 value of 63 nM. It also concentration-dependently inhibited migration against Bel-7402 cells. Importantly, tertiary sulphonamide 17a exhibited the potent antitumor activity in vivo. All these findings revealed that compound 17a might be a tertiary sulphonamide-based dual inhibitor of tubulin polymerisation and LSD1 to treat liver cancer.